2010
DOI: 10.1111/j.1600-0528.2010.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental erosion in children: a national survey

Abstract: Dental erosion was frequently present by the age of 12; the prevalence doubled by age 15 and was seen almost twice as often among boys than girls. Teeth most frequently showing signs of erosion were the lower first molars. The rapidly growing prevalence of erosion demonstrated by this nationwide survey emphasizes the need for further research into the aetiology of erosion and possible methods of preventing and treating this emerging dental problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
67
5
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 25 publications
13
67
5
12
Order By: Relevance
“…24 A more frequent occurrence of erosive lesions in males compared to females was found by Arnadottir et al and McGuire et al, and in our study the same tendency was also noticed (18.47% vs 14.86%, respectively). 25,26 All of the indices used in our study identified the same number of erosion-affected teeth but not their severity; according to the index by Lussi, the lesions limited only to the enamel involved 76 teeth, and 10 teeth w ith lesions exposing the dentin, whereas in accordance with the criteria of the index by O'Sullivan, there were 62 and 24 affected teeth, respectively. A similar inconsistency regarding the severity of erosive lesions and, moreover, differences in frequency was reported by Margaritis et al, who, for dental erosion assessment, simultaneously used 3 indices -the BEWE, Simplified Tooth Wear Index (STWI) and Evaluating Index of Dental Erosion (EVIDE).…”
Section: Discussionmentioning
confidence: 76%
“…24 A more frequent occurrence of erosive lesions in males compared to females was found by Arnadottir et al and McGuire et al, and in our study the same tendency was also noticed (18.47% vs 14.86%, respectively). 25,26 All of the indices used in our study identified the same number of erosion-affected teeth but not their severity; according to the index by Lussi, the lesions limited only to the enamel involved 76 teeth, and 10 teeth w ith lesions exposing the dentin, whereas in accordance with the criteria of the index by O'Sullivan, there were 62 and 24 affected teeth, respectively. A similar inconsistency regarding the severity of erosive lesions and, moreover, differences in frequency was reported by Margaritis et al, who, for dental erosion assessment, simultaneously used 3 indices -the BEWE, Simplified Tooth Wear Index (STWI) and Evaluating Index of Dental Erosion (EVIDE).…”
Section: Discussionmentioning
confidence: 76%
“…Although most of the reference literature shows that in Europe tooth wear is more frequent in young boys and men, in the case of our study population there was no significant difference between genders as far as this aspect is concerned. [20][21][22][23] The fact that men are more affected may be explained by their more developed masticatory muscles, their greater force of mastication, and their different eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…Bu bağlamda özellikle genç erişkinlikler arasında hazır gıdaları ve gazlı içecekleri kullanma alışkanlığı artmıştır. Birçok çalışmaya göre gelişmiş ve gelişmekte olan ülkelerin genç çocuk ve erişkinlerinde dental erozyon prevalansının arttığı gözlenmiştir [31][32][33] . Erozyon toplumun her yaş grubunda görüle-bilen yüksek prevalansa sahip eskiden olduğu gibi günümüzde de devam eden önemli bir diş problemidir.…”
Section: Erozyonun Prevalansiunclassified